2003
DOI: 10.1038/sj.onc.1206622
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial membrane permeabilization is a critical step of lysosome-initiated apoptosis induced by hydroxychloroquine

Abstract: Hydroxychloroquine (HCQ) is a lysosomotropic amine with cytotoxic properties. Here, we show that HCQ induces signs of lysosomal membrane permeabilization (LMP), such as the decrease in the lysosomal pH gradient and the release of cathepsin B from the lysosomal lumen, followed by signs of apoptosis including caspase activation, phosphatidylserine exposure, and chromatin condensation with DNA loss. HCQ also induces mitochondrial membrane permeabilization (MMP), as indicated by the insertion of Bax into mitochond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
270
3
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 356 publications
(300 citation statements)
references
References 52 publications
26
270
3
1
Order By: Relevance
“…Pretreatment with bafilomycin A1 reduces the frequency of lysosomal release of cathepsin B induced by lysosomotropic amines such as hydroxychloroquine. 25 In the present study, however, cathepsin B was released by combining TMZ with bafilomycin A1, although TMZ alone or bafilomycin A1 alone did not affect the release of cathepsin B. These findings suggest that the presence of bafilomycin A1 may correlate accumulation of autophagic vacuoles induced by TMZ with perturbation of lysosomal function, leading to induction of apoptosis via activation of caspase-3.…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…Pretreatment with bafilomycin A1 reduces the frequency of lysosomal release of cathepsin B induced by lysosomotropic amines such as hydroxychloroquine. 25 In the present study, however, cathepsin B was released by combining TMZ with bafilomycin A1, although TMZ alone or bafilomycin A1 alone did not affect the release of cathepsin B. These findings suggest that the presence of bafilomycin A1 may correlate accumulation of autophagic vacuoles induced by TMZ with perturbation of lysosomal function, leading to induction of apoptosis via activation of caspase-3.…”
Section: Discussioncontrasting
confidence: 76%
“…Recently, it has been demonstrated that some apoptotic cell death pathways have a sign of lysosomal membrane permeabiliza- tion such as the release of cathepsin B from the lysosomal lumen, followed by signs of apoptosis including caspase activation. 25 Therefore, we finally determined if combination of TMZ and bafilomycin A1 released cathepsin B from lysosome. As shown in Figure 7c, cathepsin B colocalized with Lamp-1 (the lysosomal membrane marker) in untreated U373-MG cells (control).…”
Section: Characterization Of Tmz/bafilomycin A1-induced Cell Deathmentioning
confidence: 99%
“…Similarly, it has been found that lysosomotropic toxins fail to kill cells when the Bax and/or Bak genes are removed from the system or when mitochondrial membranes are sealed by overexpression of Bcl-2 (or the strictly mitochondrion-specific vMIA protein from Cytomegalovirus). 10,11 In such a system, the absence of Bax and/or Bak or the presence of Bcl-2 or vMIA fails to affect the redistribution of cathepsins B and D, yet does block the release of mitochondrial death effectors, including cytochrome c. 10,11 These data point to an obligatory participation of mitochondria in the transmission of lethal signal initially perceived at the lysosomal level. …”
Section: A Lethal Cascade Linking Lysosomes To Mitochondriamentioning
confidence: 99%
“…1 In several other models of LMP-mediated cell death, the inhibition of individual cathepsins (or their knockout) is not sufficient to block the activation of Bax. 10,11 Thus, several cathepsins (and perhaps even other lysosomal hydrolases) may be able to constitute the link between LMP and MMP. Indeed, cysteine cathepsins B, H, L, S, and K have recently been shown to cleave and activate the Bax-activating Bcl-2 family member, Bid, in vitro (Boris Turk, personal communication), and the TNF-induced MMP in hepatocytes depends on the activity of cathepsin B rather than cathepsin D. 5 Such variations in the requirement of individual cathepsins between the diverse apoptosis models may reflect differences in the expression levels of cathepsins themselves or their endogenous cathepsin inhibitors, which are highly cell type dependent.…”
Section: Missing Links Between Lysosomes and Mitochondriamentioning
confidence: 99%
“…These signals usually eventually activate the mitochondrial pathway too (63). Apoptosis as a result of mitochondrial permeabilization can also be triggered following lysosomal permeabilization (64) and accumulating evidence indicates that there may be direct linkages between lysosomal functions and both apoptosis and autophagy (65). For example, it was recently reported that a transmembrane protein called TMEM166 that is associated with lysosomes and the ER as been reported to regulate apoptosis and autophagy (66).…”
Section: Regulation Of Apoptosismentioning
confidence: 99%